Simple limbal epithelial transplantation for recurrent pterygium: A case series - Zale Mednick; Tanguy Boutin; Adi Einan-Lifshitz; Nir Sorkin; Allan Slomovic (American Journal of Ophthalmology Case Reports, 2018)
Purpose: Pterygium recurrence is a common complication of pterygium removal. Multiple surgical and medical approaches have been utilized to reduce recurrence rates. The present case series proposes a novel way to treat recurrent pterygia, by using the simple limbal epithelial transplantation (SLET) technique. Observations: The cases of four patients who presented with recurrent pterygium were reviewed. In all four of the cases reported, the SLET procedure went without complication. There were no significant recurrences at each of the patient's most recent follow-up visits. Conclusions and importance: This is the first report of SLET being used as a treatment modality for recurrent pterygium. Further studies are required to more reliably demonstrate the utility of the procedure in this clinical circumstance, but our results are encouraging that in select patients, this may be a viable option in treating aggressive recurrent pterygia. Keywords: Simple limbal epithelial transplantation (SLET), Recurrent pterygium, Cornea, Conjunctiva, Stem cells